2017
DOI: 10.1002/cphc.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐Doped Monolayer Graphene with Boron, Nitrogen, Aluminum, Silicon, Phosphorus, and Sulfur

Abstract: The structure, stability, electronic properties and chemical reactivity of X/B/N triple-doped graphene (TDG) systems (X=Al, Si, P, S) are investigated by means of periodic density functional calculations. In the studied TDGs the dopant atoms prefer to be bonded to one another instead of separated. In general, the XNB pattern is preferred, with the exception of sulfur, which favors the SBN motif. The introduction of a third dopant results in a negligible decrease of the cohesive energies with respect to the dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 69 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…However, the likely dendrite formation will result in poor charge/discharge rate . Fortunately, the chemistry of graphene can easily be modified by certain techniques, among which doping is regarded as the simplest and efficient way . It is advantageous to dope graphene with the neighbors (B and N) and next neighbors (Be and O) atoms due to the relatively similar atomic radii of these atoms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the likely dendrite formation will result in poor charge/discharge rate . Fortunately, the chemistry of graphene can easily be modified by certain techniques, among which doping is regarded as the simplest and efficient way . It is advantageous to dope graphene with the neighbors (B and N) and next neighbors (Be and O) atoms due to the relatively similar atomic radii of these atoms .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Fortunately, the chemistry of graphene can easily be modified by certain techniques, among which doping is regarded as the simplest and efficient way. [21][22][23][24][25][26] It is advantageous to dope graphene with the neighbors (B and N) and next neighbors (Be and O) atoms due to the relatively similar atomic radii of these atoms. [5,21,24] Additionally, the toxicity of Be is well-known but this cannot restrict the use of Be in practical applications such as in optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…[15] In the last few years, graphene and graphene oxide (GO;a no xidized form of graphene) have becomeimportant in many research studies owing to their extraordinary electronic,mechanical, and biostructural characteristics. [16][17][18][19][20] The aggregation of amyloid b (Ab)w ith graphene andG O has been studied experimentally. [21][22][23] Mahmoudi and colleagues demonstrated that, through adsorption of amyloid monomers, large flakeso fG Os heets inhibit Ab fibrillization.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by silicon-based technologies,t he doping route has been recently affirmed as an effective strategy to prepare organic semiconductors with tailored optoelectronic properties. [1] Thec ontrolled replacement of carbon atoms with isostructural heteroatoms [2] gives access to congeners of sizedefined molecular graphenes. [3] In particular, the isolation of extended polycyclicaromatic hydrocarbons (PAHs) featuring zig-zag edges [4] such as m,n-perifusenes ( Figure 1, m and n designates the number of fused rings) [5] is challenging owing to their susceptibility toward O 2 .…”
mentioning
confidence: 99%
“…Consistently,t he emission spectra shown in Figure 4r eflect the same trend, with the intense emission peak of 1 (l max = 540 nm, F fl = 0.38) significantly red-shifted with respect to that of 11 (l max = 457 nm, F fl = 0.48), with nanosecond lifetimes (Table 1). [10,22] Next, we examined the redox properties by cyclic voltammetry (CV) measurements and differential pulse voltammetry (DPV) ( (5), pentane (11), and toluene (1). [25]…”
mentioning
confidence: 99%